Effect of maleated anhydride on mechanical properties of rice husk filler reinforced PLA matrix polymer composite - Siregar, Januar Parlaungan; M. R. M., Rejab; Jamiluddin, Jaafar; Mohd Hazim, Mohd Hamdan; Bachtiar, Dandi; Tezara, C. (Springer, 2019)
Polylactic acid (PLA) formulated from corn starch has a bright potential to replace the non-renewable petroleum-based plastics. The combination of PLA and natural fibre has gained interest due to its unique performance, as reported in many researches and industries. Meanwhile, rice husk produced as the by-product of rice milling can be utilised, unless it is turned completely into waste. Therefore, in the present study, the rice husk powder (RHP) was used as a filler in the PLA, So to determine the influence of the filler loading on the mechanical properties of the PLA composite. A coupling agent was selected for treatment from two options, i.e., maleic anhydride polypropylene (MAPP) and maleic anhydride polyethylene (MAPE), by applying the agents with various loading contents, such as 2, 4 and 6 wt%. The composite was fabricated by using the hot compression machine. Both the treated and untreated RHP–PLA composites were characterised via the tensile, flexural and impact strength tests. The increase in the RHP loading content led to the decrease in the tensile and flexural strengths. The applications of the coupling agents (MAPE and MAPP) did not improve the tensile and impact strengths, but the flexural strength was enhanced.